2020
DOI: 10.1371/journal.ppat.1008365
|View full text |Cite
|
Sign up to set email alerts
|

B cells infected with Type 2 Epstein-Barr virus (EBV) have increased NFATc1/NFATc2 activity and enhanced lytic gene expression in comparison to Type 1 EBV infection

Abstract: Humans are infected with two distinct strains (Type 1 (T1) and Type 2 (T2)) of Epstein-Barr virus (EBV) that differ substantially in their EBNA2 and EBNA 3A/B/C latency genes and the ability to transform B cells in vitro. While most T1 EBV strains contain the "prototype" form of the BZLF1 immediate-early promoter ("Zp-P"), all T2 strains contain the "Zp-V3" variant, which contains an NFAT binding motif and is activated much more strongly by B-cell receptor signalling. Whether B cells infected with T2 EBV are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 88 publications
5
37
0
1
Order By: Relevance
“…In our experiments here, in most cases we used P3HR1 virus derived from a P3HR1 BL cell clone that is lacking the W-Zhet genomes, making it unlikely that that these particles are required for P3HR1-mediated lymphomagenesis. Nevertheless, since we found that the P3HR1 induced tumors (particularly the EBNA-LP-high/LMP1-low foci) are highly lytic (consistent with our recent finding that type 2 EBV is much more lytic in B cells compared to type 1 EBV) [47], it is quite possible that lytic infection plays an important role in promoting the ability of P3HR1 to induce lymphomas in CBH mice.…”
Section: Plos Pathogenssupporting
confidence: 91%
See 4 more Smart Citations
“…In our experiments here, in most cases we used P3HR1 virus derived from a P3HR1 BL cell clone that is lacking the W-Zhet genomes, making it unlikely that that these particles are required for P3HR1-mediated lymphomagenesis. Nevertheless, since we found that the P3HR1 induced tumors (particularly the EBNA-LP-high/LMP1-low foci) are highly lytic (consistent with our recent finding that type 2 EBV is much more lytic in B cells compared to type 1 EBV) [47], it is quite possible that lytic infection plays an important role in promoting the ability of P3HR1 to induce lymphomas in CBH mice.…”
Section: Plos Pathogenssupporting
confidence: 91%
“…EBNA2-deleted P3HR1 EBV causes HLs and DLBCLs in humanized mice Similar to our recent report comparing the phenotypes of type 1 versus type 2 EBV infected lymphomas in CBH mice [47], we found that type 1 B95.8 infected lymphomas express much more LMP1 than type 2 AG876 infected lymphomas, while AG876 infected lymphomas express much more of the BZLF1 lytic viral protein than B95.8 infected lymphomas (Fig 8A). In contrast, lymphomas induced by P3HR1 (although it is a type 2 EBV strain) express much more LMP1 compared to the AG876 type 2 control lymphomas, consistent with the IHC results in Fig 3 and confirming that some P3HR1 virus infected cells have type II latency.…”
Section: Plos Pathogenssupporting
confidence: 90%
See 3 more Smart Citations